Rare Pathology Case Report: Low-Grade Endometrial Stromal Sarcoma Forming Sex Cord- and Endometrioid Gland-Like Differentiation in Metastatic Foci - Haneen Al-Maghrabi; Ghadeer Mokhtar; Jaudah Al-Maghrabi (Hindawi Limited, 2024)
Low-grade endometrial stromal sarcomas (LGESSs) are indolent tumors with a slow progression rate that tend to recur locally. They represent up to 10% of all primary sarcomas of the uterus and endometrium and only 0.2% of all genital tract tumors. They are commonly present in a younger demographic compared to other uterine tumors, with patients' ages typically between 42 and 58 years old. Although the overall 5-year survival rate is excellent, it has a natural history of delayed metastases which may manifest even decades after the disease was first diagnosed. They typically present as poorly defined lesions infiltrating the myometrium, along with extensive engagement of surrounding vascular structures. LGESS may display variants of different morphologies such as smooth muscle, fibromyxoid, sex cord-like, and endometrioid-type gland differentiation. These variations can pose a diagnostic challenge. The occurrence of this differentiation in a metastatic focus rather than in the primary tumor is seldom recorded in the literature. We present a case of a 51-year-old lady with a history of LGESS who was treated with surgery and radiotherapy and then presented after 12 years with an inferior vena cava (IVC) mass, which was confirmed histologically to be metastatic LGESS. Immunohistochemistry studies reveal strong positivity for CD10, WT1, and PR. These markers were negative in the sex cord and endometrioid gland-like differentiation counterparts. The patient had her initial follow-up appointment after the IVC mass resection, and she was in good health with no complications. To the best of our knowledge, this case represents a unique instance of metastatic LGESS exhibiting both sex cord and endometrioid gland-like differentiation that has not been observed in the primary tumor.